2008
DOI: 10.1161/circulationaha.107.742155
|View full text |Cite
|
Sign up to set email alerts
|

Death Without Prior Appropriate Implantable Cardioverter-Defibrillator Therapy

Abstract: Background-Implantable cardioverter-defibrillators (ICDs) improve survival in selected patients with left ventricular systolic dysfunction in randomized trials. Competing death without prior appropriate ICD therapy might preclude benefit from ICD implantation in a less selected routine-care population. Methods and Results-We selected all patients with ischemic or dilated cardiomyopathy with an ICD implanted for primary or secondary prevention from a single-center prospective registry between 1994 and 2006. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 36 publications
4
87
0
4
Order By: Relevance
“…In light of this, alternative analytic approaches that account for the occurrence of such competing events have been developed to estimate the cumulative incidence [1,8]. While these issues are mathematically demonstrated and have been illustrated in various medical domains [2,3,6], they have received less attention in orthopaedic research until recently [7,8]. But while some work has been done in individual datasets [8], to my knowledge, no study has taken a broader look at the influence of the phenomenon of competing risks on Kaplan-Meier survivorship estimates across orthopaedics more generally.…”
Section: T Is Well Known That the Kaplan-mentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, alternative analytic approaches that account for the occurrence of such competing events have been developed to estimate the cumulative incidence [1,8]. While these issues are mathematically demonstrated and have been illustrated in various medical domains [2,3,6], they have received less attention in orthopaedic research until recently [7,8]. But while some work has been done in individual datasets [8], to my knowledge, no study has taken a broader look at the influence of the phenomenon of competing risks on Kaplan-Meier survivorship estimates across orthopaedics more generally.…”
Section: T Is Well Known That the Kaplan-mentioning
confidence: 99%
“…Two types of analyses can be carried out, both being methodologically correct, but with different aims and sometimes different results. Indeed, one could assess whether the cumulative incidence of revision is higher with one type of implant as compared to another, or whether the cause-specific hazard of revision-the instantaneous rate of revision among the patients still alive with their implant-is higher with the first type of implant as compared to the other [3]. In the classical survival setting where patients can only fail from one cause (overall survival analysis), both analyses are equivalent, and are commonly carried out using a Cox proportional hazards model.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The majority of patients who died prior to appropriate ICD therapy had a primary prevention indication. Despite the effectiveness of terminating ventricular tachyarrhythmias by the ICD, competing non-cardiac comorbidity is associated with increased mortality [75]. Furthermore the effect of renal function on ICD efficacy was assessed in a retrospective analysis from MADIT II [76].…”
Section: Comorbiditymentioning
confidence: 99%
“…In particular, the mechanical stress due to the electrical conversion therapy received before, would have caused an additional insult to the underlying myocardium. This could act as a potential substrate predisposing the patient for further serious ventricular tachyarrhythmia [16]. Despite this increased risk of malignant arrhythmias, there was no increased mortality in ICD recipients who Prior case series have shown that many SVT can progress to VT/VF causing SCD [17].…”
Section: Scd-heft (Sudden Cardiac Death In Heart Failurementioning
confidence: 99%